Theoretical Analysis and Prediction of Overfeed Sewing Shrinkage of Wool-type Fabrics (Journal of Fiber Bioengineering and Informatics, 2018)
Overfeed is referred to two pieces of fabrics of different lengths being joined together with a thread by sewing processing. In overfeed sewing, the differences in mechanical properties of fabrics are vital factors contributing to the shrinkage of the finished fabric. Based on theory of material mechanics, the relationship model between overfeed sewing shrinkage and mechanical properties including bending modulus of the long fabric, stretch coefficient of the short fabric and the overfeeding quantity was established in this paper, and experiments were carried out to verify the relationship model. The obtained results indicated a good linear correlation between the calculated values of the model and the actual tested values. This model can provide a new method for predicting overfeed sewing shrinkage of wool-type fabric.
Keywords: Wool-type fabric; overfeed sewing shrinkage; bending modulus; stretch coefficient; FAST instrument